Limits and perspectives for the assessment of anxiety and fear of COVID-19 in pregnant women [Response To Letter] - Muñoz-Vela, Francisco Javier (2023)
The authors would like to express sincere gratitude for the thoughtful and constructive feedback provided in this letter regarding the manuscript titled “Assessment of Levels of Anxiety and Fear of Covid-19 in a Population of Pregnant Women in Spain”. First of all, the assessments of the strengths and contributions of our research are welcomed; following this, the comments and suggestions have been thankfully received by the authors. The importance of highlighting these limita tions and opportunities for improvement is appreciated as, perhaps, these were not firmly underlined in the article. This study is the result of a series of academic research1,2 whose main aim was to improve the quality of life of pregnant women. Given this, all comments are greeted and will surely influence further investigations. Consequently, it is true that online survey administration eliminates the need for direct supervision, thus fostering honesty and freedom of response among the subjects in our sample. In the same vein, collecting data only in certain locations in Spain could affect the generalisability of the data. It is recognised the importance of obtaining a more comprehensive understanding of the variables studied in diverse geographical regions in Spain. The absence of the cultural variable as a mediator in our study is indeed a reasonable limitation, and it may have a potential impact on the interpretation of cultural constraints related to vaccine apprehension in certain nations. So, it is agreed that future research should incorporate the analysis of variables related to the cultural and religious context and should also incorporate mixed research methods that allow in-depth interviews3 with the sample in order to strengthen4 data collection on a topic as intricate as pregnant women’s mental health. In conclusion, this study undeniably provides valuable information that is relevant for clinical practice, intervention development, and evaluation of emotional symptoms in pregnant women. The identified limitations will serve as guides for future research in this same field of study. By adhering to recommended research and sampling strategies, upcoming studies can be built, allowing for improved robustness and applicability of the findings